Lessons learned from studying third-party data leaks in web services - Rauti, Sampsa (United States, 2025)
The rise of digitalization has led to a surge in the utilization of web services. Online services offer a convenient way to carry out many everyday tasks. However, third-party web analytics used in many essential web services cause privacy issues as confidential personal data may inadvertently be transmitted to these third parties. In this paper, we examine the reasons for third-party data leaks in web-based services from a software engineering point of view based on our earlier studies as well as the existing literature. We also offer several recommendations and guidelines for developers to alleviate these privacy issues in the future.
ICISE '23 : Proceedings of the 2023 8th International Conference on Information Systems Engineering